Do medo da violência à "condominiarização" das cidades brasileiras: sobre as consequências sócio-espaciais da modificação da legislação federal do solo urbano - Daniela Batista Lima Barbosa (2008)
The fear of violence has been responsible for the proliferation of exclusive condominiums in Brazil and theirs equivalents in several countries (gated communities in the United States and other English-speaking countries; barrios cerrados in Argentina; security parks in South Africa). In Brazil, country that combines rapid and complex urbanization with large socio-economic asymmetries, the run for the condominiums have been one of the most striking characteristicsof the metropolization process since the 1970s and 80s; reaching, during the 1990s, even many medium cities. It happens, that many of these condominiums are, by the current legislation, irregulars, because they are not true horizontal condominiums (i.e., one single real state already sold to the end-user with the habitation units already built, with no true public areas within the terrain and each buyer owns just an ideal fraction), but medium and high status closed subdivisions (and, according to the Federal Law of Division of the Urban Land, subdivisions, because they have public areas which domains belongs to the State within them, they cannot be closed). Aiming to circumvent the problem of the illegality of the great majority of these self-segregated habitats, a process of legislature revision, called Law of Urban Territorial Responsibility, has been in course for a few years. The revision of the Law 6,766/79, in what it regards the division of urban land and its social-space consequences in Brazilian cities, constitutes the subject of the present study. And the main question that seems to arise, and that constitutes the guiding problem of the present study, is concerningthe covert of the effects that this new law intends to impose, taking inconsideration the causes of its promulgation, the responsible agents, and its socialspace consequences for the Brazilian cities. What impacts will this new legal hallmark bring to the urban life and spaces, depending on how it is approved?